Pengaruh Berbagai Formulasi Pemupukan Terhadap Pertumbuhan Dan Hasil Cabai Rawit Varietas Crv 212 Di Tanah Ultisol - Noraina, Noraina; Susanti, Hilda (Jurusan Agronomi, Fakultas Pertanian, Universitas Lambung Mangkurat, 2026)
Research on the effect of various fertilizer formulations on the growth and yield of cayenne pepper on ultisol soil was conducted from February to July 2025 at the research land of the Agronomy Study Program, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan. The study used a single factor Completely Randomized Design (CRD). The factors used were Fertilization Formulation with 4 treatment levels, namely, p0 = basal fertilizer, p1 = cayenne pepper fertilizer CRV 212 variety, p2 = cayenne pepper fertilizer Hiyung variety, p3 = National cayenne pepper fertilizer. The treatment was repeated 5 times to obtain 20 experimental units. Each experimental unit contained 2 plant samples so that a total of 40 plants were obtained. The parameters observed were increase in plant height (cm), increase in the number of leaves (blades), stem diameter (mm), number of branches (fruits), age of first flowering (DAP), age of first fruiting (DAP), age of first harvest (DAP), number of harvested fruit (fruit), harvested fruit weight (g), fruit length (cm), and fruit diameter (mm). The results of the study showed that the fertilizer formulation had a significant effect on the increase in plant height, the age of the first harvest and had a very significant effect on stem diameter.